Tularemia induces different biochemical responses in BALB/c mice and common voles - Banďouchová, Hana; Sedláčková, Jana; Pohanka, Miroslav; Novotný, Ladislav; Hubálek, Martin; Treml, František; Vitula, František; Pikula, Jiří (BMC infectious diseases, 2009)
BACKGROUND: Both BALB/c mice and common voles (Microtus arvalis) are considered highly susceptible to tularemia. However, the common vole is reported to harbour Francisella tularensis in European habitats as well as to survive longer with chronic shedding of the bacterium. The purpose of the present study was to compare the response of these two rodents to a wild Francisella tularensis subsp. holarctica strain infection. METHODS: Rodents were evaluated for differences in the total antioxidant capacity derived from low-molecular-weight antioxidants, biochemistry including lipid metabolism, tissue bacterial burdens and histopathology following experimental intraperitoneal infection with 160 colony forming units (CFU) pro toto. RESULTS: Bacterial burdens in common voles started to develop later post-exposure and amounted to lower levels than in BALB/c mice. Elevation of liver function enzymes was more pronounced in mice than common voles and there were marked differences in lipid metabolism in the course of tularemia in these two species. Hypertriglyceridemia and hypercholesterolemia developed in mice, while physiologically higher levels of triglycerides and cholesterol showed a decreasing tendency in common voles. On the other hand, the total plasma antioxidant capacity gradually dropped to 81.5% in mice on day 5 post-infection, while it increased to 130% on day 6 post-infection in common voles. Significant correlations between tissue bacterial burdens and several biochemical parameters were found. CONCLUSION: As differences in lipid metabolism and the total antioxidant capacity of highly susceptible rodent species were demonstrated, the role of triglycerides, cholesterol and antioxidants in tularemic sepsis should be further investigated.
Keywords: Animals; cholesterol; Antioxidants; nemoci hlodavců; Rodent Diseases; triglyceridy; tularemie; Triglycerides; Lipid Metabolism; Mice; Tularemia; Mice, Inbred BALB C; Arvicolinae; myši; metabolismus lipidů; Cholesterol; myši inbrední BALB C; antioxidancia; zvířata